2014
DOI: 10.5897/ajbr12.095
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipids and oxidized low density lipoprotein levels in sickle cell disease: Assessment and pathobiological significance

Abstract: One hundred and eighteen (118) subjects aged 15 to 36 years divided into control subjects (AA n = 42), heterozygous sickle cell patients (AS n = 33) and homozygous sickle cell patients (SS n = 43) were investigated for a lipid profile including the measurement of oxidized low density lipoprotein (LDL) to assess the risk of early atherosclerosis in sickle cell disease. The results show that total, high density lipoprotein (HDL) and LDL plasma cholesterol levels are significantly lower in the sickle cell patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…These results are in keeping with values in adult African -American SCA patients reported in 2003 in which there was a higher than normal reference in plasma triglyceride but lower values of total cholesterol, high density lipoprotein (HDL) and low density lipoprotein (LDL) [39]. The findings are also in keeping with data of Indians in 2016 [40] and Senegalese in 2014 [41]. By implication, hypocholesterolemia, low LDL and HDL and higher values of TG and VLDL reported severally in SCA patients may not be related to age, race, socio-economic status or diet but may be genetic and related to the pathophysiology of the disease.…”
Section: Discussionsupporting
confidence: 90%
“…These results are in keeping with values in adult African -American SCA patients reported in 2003 in which there was a higher than normal reference in plasma triglyceride but lower values of total cholesterol, high density lipoprotein (HDL) and low density lipoprotein (LDL) [39]. The findings are also in keeping with data of Indians in 2016 [40] and Senegalese in 2014 [41]. By implication, hypocholesterolemia, low LDL and HDL and higher values of TG and VLDL reported severally in SCA patients may not be related to age, race, socio-economic status or diet but may be genetic and related to the pathophysiology of the disease.…”
Section: Discussionsupporting
confidence: 90%
“…COA Carboxylase and reduced the activity of cholesterol Acyltransferase and lecithin and inhibiting the activity of lipoprotein lipase and liver lipase activity that led to increased synthesis of vL DLc and decreased the concentration of HDL-C [21]. In this study found a strong significant effect between ox-LDL and total cholesterol ratio and known that HDL levels are associated with age in women, HDLcholesterol levels increase progressively to the fifth decade and then decrease with menopause, the mechanism may influence the data on HDL-C concentration [22]. One of the more prominent markers of oxidative stress in DM is ox-LDL ; increased production of free oxygen radicals, higher ox-LDL along with stimulation of ox-LDL uptake by macrophages and the ensuing promotion of early atherosclerotic changes might be contributed by insulin resistance (IR);hyperglycemia is associated by increased inflammatory burden and increased lipid peroxidation ,all leading to inhanced macrophage foam cell formation , low density lipoprotein (LDL) oxidation by macrophages was increased due to the activation of several pro-oxidant systems as well as the depletion of antioxidants [23] ox-LDL and oxidation ratio of LDL (ox-LDL/TC, ox-LDL/HDL-C, and ox-LDL/LDL-C) are closely related with CHD and they are better biomarkers for discrimination between patients with coronary heart disease and healthy [24].…”
Section: Resultssupporting
confidence: 49%
“…Prior in vitro studies have indicated that lipoproteins contribute significantly to the consumption of plasma heme and lipid oxidation (30). Chronic hemolysis and episodic increases in hemolytic rate occur in SCD in the setting of depleted scavenger proteins (Hp and Hpx), which likely renders lipoproteins more prone to oxidative modification and contributes to a higher ratio of oxidized to reduced lipids in the plasma of patients with SCD (1,4).…”
Section: Discussionmentioning
confidence: 99%